Computer Aided Model for an Off-grid Photovoltaic System Using Batteries Only - Emil Lazarescu; Flaviu M. Frigura-Iliasa; Marius Mirica; Mihaela Frigura-Iliasa; Lia Dolga; Hannelore E. Filipescu (IAES Indonesia Section, 2018)
This article will present an off-grid photovoltaic energy system based on a photovoltaic element (PV), or a group of PVs, integrated in a solar battery (SB), directly connected to an electrical battery (EB) having no DC-DC adapter (use of adapters is the most common solution existing now on in this domain). This SB must be properly adjusted to the EB, not only as voltage, but it must provide also the same amount of energy as the system when operating at its classically detected maximum power operating point. This proposed technical solution is more economically justified, compared to the classic one: SB+DC-DC+EB, due to the simple fact that the DC-DC converter is no longer required at all. A simple mathematical model for the current-voltage characteristics is also presented, followed by a comparison between the classic DC-DC converter-based solution and the newly proposed one, without DC-DC converter.